Pengaruh Good Corporate Governance Terhadap Persistensi Laba - Karina Steffany; yulius Jogi Christiawan (Business Accounting Review, 2016)
This study aims to prove the influence of good corporate governance on earnings persistence. The research was conducted on companies that received a rating CGPI by IICG in cooperation with SWA magazine in Indonesia within the observation period of 2010 until 2014 with a sample of 54 observations. Earnings persistence was measured by using regression slope coefficient of earnings per share. The control variables used in this study were the size of the company, cash flow volatility, volatility of sales, operating cycle, and proportion of negative earnings.The results of this study indicated that good corporate governance had no affect on earnings persistence. The size of the company had a positive effect on the persistence of earnings, operating cycle and the proportion of negative earnings had a negative affect on earnings persistence. Furthermore, the results also showed that the volatility of cash flow and sales volatility had no affect on the persistence of earnings